Species specific polymerase chain reaction (PCR) assay for identification of pig (Sus domesticus) skin in “Rambak” crackers - Erwanto, Yuny (2016)
“Rambak” is the animal skin crackers product which one of the popular food products derived from the animal by-products in Indonesia. For the religion reasoning the presence of pig derivatives in any food products is prohibited for Moslem community. For this reason, the analytical methods offering accurate and sensitive results are highly needed in order to assure the halal authenticity of food. The objectives of this research is to developed the pig species specific primer for identification of specific pig deoxyribonucleic acid (DNA) in “Rambak” cracker using polymerase chain reaction ( PCR) analytical methods. This research used were four kinds of animal skin crackers in individual or mixture samples. Skin mixture were prepared and divided into nine formulas as follows 1) 100% pig; 2) pig 90%: cattle 10%; 3) pig 75%: cattle 25%; 4) pig 50%: cattle 50%; 5) pig 25%: cattle 75%; 6) pig 10%: cattle 90%; 7) pig 1%: cattle 99%; 8) pig 0.1%: cattle 99,9% ; and 9) 100% cattle. The same formula also prepared in mixture between pig skin with buffalo and goat skin. DNA were isolated from the cracker products and applied in PCR using perimer specific. The optimized PCR assay was subsequently validated for its specificity with deoxyribonucleic acid (DNA) extracted from cattle, buffalo, goat and pig in individual or mixture samples. Results showed the primers designed generated specific fragment of 510 bp length for pig cytochrome b DNA. The specificity of the primers was tested on four animal species including pig, cattle, buffalo and goat species. Analysis of experimental mixture meat demonstrated that 0.1% of pig tissues could be detected using specific primer. The specificity of pig-specific PCR provides a valuable tool for identification of pig skin and to avoid its fraudulent substitution and adulteration.